A lost collection (1989–1994) of reptiles, birds and mammals of the Syrian Jazira (Syrian Arab Republic). Issue 1 (April 2016) - Masseti, Marco
Abstract : Basmafasal is a suburb of the town of Deir ez-Zor, located in that part of northern Syrian Mesopotamia known as the Jazira (al-Jazīrah), which lies in between the Euphrates and Khabur rivers. During the second half of the 1980s, a collection of mounted mammals, birds and reptiles was made by a local man, Abu Rabi c, with the aim of representing the animal life of the region. The collection comprised many species of mammals, including several specimens of Taphozous nudiventris (naked-bellied tomb bat), Felis chaus, Lutra lutra, Hyaena hyaena, Sciurus anomalus (Persian squirrel), Hystrix indica (Indian crested porcupine), and Gazella subgutturosa marica, while birds were represented by about 200 taxa. With hundreds of exhibits, the Abu Rabi c collection was representative of the biodiversity of the Jazira. It was destroyed in 1994.